Janko Polić Kamov – Towards the Avant-Garde - Polić, Iva (Anafora, 2023)
The paper analyses the status of Janko Polić Kamov in Croatian literature. Although Kamov is usually referred to as a representative of Croatian Futurism, his work anticipated the avant-garde on the whole. His contemporaries and relevant figures in Croatian literature in the first half of the twentieth century failed to recognise and/or acknowledge Kamov as one of the originators of not only the Croatian but European avant-garde as well. Today, his significance is widely acknowledged, but he remains quite unknown to the general public in Croatia, or known exclusively as a futurist, or even a “foul-mouthed writer.” The paper looks into the features of Futurism in general and into the work of Kamov. We conclude, based on the examples presented and the relevant literature on Kamov, that his work cannot be attributed solely to Futurism but also to other avant-garde movements such as Expressionism and Surrealism. Kamov did indeed argue and fight for artistic freedom, and against social and literary conventions. However, his work is not socially-engaged: it is primarily an expression of his inner world and based on his personal experience. Due to this nonconformist attitude, he came to be referred to as the anti-poet, a name by which he, surprisingly or not, goes even today – more than a hundred years after his death.